Improvements in habitability and housing satisfaction after dwelling regeneration in social housing complexes. The RUCAS study - González, F.; Baeza, F.; Valdebenito, R.; Sánchez, B.N.; Diez-Roux, A.; Vives, A. (Social science & medicine (1982), 2024)
Housing is a pressing problem worldwide and a key determinant of health and wellbeing. The right to adequate housing, as a pillar of the right to an adequate standard of living, means more than a roof to live under. Adequate means the dwelling must fulfill material functions and psychosocial functions, thus contributing to dwellers health and wellbeing. Social housing policies aim to fulfill the right to housing, but frequently fail in fulfilling the right to it being adequate. This study capitalizes on the implementation of a national urban regeneration program in two social housing villas in central Chile (one in Santiago, in the central valley, the other in Viña del Mar, a coastal city) to run a natural experiment assessing the impact of dwelling renovation on several dimensions of perceived habitability and housing satisfaction among the -mostly female-household homemakers. We use 5 waves of survey data collected with a step-wedge design to estimate the association between a time-varying exposure status (the intervention) and 7 binary outcomes for habitability and 5 for housing dissatisfaction, including overall housing satisfaction. We use Poisson regression models with robust variance and a random intercept at the respondent level. At baseline, reports of poor habitability and dissatisfaction across all features were markedly high, the highest levels of dissatisfaction being with acoustic insulation and dwelling size in both villas, and with indoor temperature in Santiago. The intervention resulted in statistically significant and markedly large improvements in reported habitability and dissatisfaction relative to those housing components targeted by the intervention, as well as with overall dwelling satisfaction in both study cases. Implications are, first, that the policy response to quantitative housing deficits must not overlook housing quality; second, that housing renovation appears as a promising intervention for qualitative housing crises; third, that while improvements in habitability and satisfaction are specific to the interventions in place, overall housing satisfaction can improve in more limited, tailored, dwelling renovation interventions. Social housing renovation in Latin America appears as a promising intervention to improve quality of life among the urban poor dwellers and reduce inequalities in health related to housing conditions. •Study of reported habitability and housing satisfaction among urban poor homemakers.•First longitudinal assessment of formal social housing renovation in Latin America.•Housing renovation can positively impact quality of life and wellbeing.•Results stress the need to addressing the qualitative housing crisis.•General satisfaction improved in all cases, despite different interventions.